2012
DOI: 10.1213/ane.0b013e31825018e2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Sodium Content of Local Anesthetics for Peripheral Nerve Blocks

Abstract: Dilution with 5% dextrose provides earlier onset of axillary brachial plexus block with ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…In a systematic review, dextrose prolotherapy found to be effective in chronic musculoskeletal conditions, particularly tendinopathies and osteoarthritis after three to six months of treatment. [ 2 ] In our case, we found an early improvement in pain, and the pain reduction was 50% (VAS decreased from 10 to 5) at 1 h. Dhir et al[ 3 ] demonstrated that sensory nerve block was started earlier with 5% dextrose plus local anesthetic than saline plus local anesthetic. In another study, it was suggested that 5% dextrose was effective in reducing the pain after 15 min and it could affect the sensory nerves expressing the transient receptor potential vanilloid-1 (TRPV-1) channel in a different way.…”
supporting
confidence: 56%
“…In a systematic review, dextrose prolotherapy found to be effective in chronic musculoskeletal conditions, particularly tendinopathies and osteoarthritis after three to six months of treatment. [ 2 ] In our case, we found an early improvement in pain, and the pain reduction was 50% (VAS decreased from 10 to 5) at 1 h. Dhir et al[ 3 ] demonstrated that sensory nerve block was started earlier with 5% dextrose plus local anesthetic than saline plus local anesthetic. In another study, it was suggested that 5% dextrose was effective in reducing the pain after 15 min and it could affect the sensory nerves expressing the transient receptor potential vanilloid-1 (TRPV-1) channel in a different way.…”
supporting
confidence: 56%
“…Only one study systematically evaluated the rates of postoperative neurologic symptoms persisting beyond 180 days, and it did not identify any among 95 participants [164]. One additional study that followed all postoperative neurologic symptoms to completion [44] identified a single participant with persistent sensory deficit 3 years after axillary peripheral nerve blockade. Among participants with symptoms occurring or persisting at 90 days or beyond, all received either an axillary or interscalene peripheral nerve blockade (Table 6), and all participants reported sensory symptoms, with motor symptoms concurrently reported in 13% (4 of 31).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we captured and included 22 additional articles following manual search of citations and bibliographies from 70 systematic reviews and meta-analyses. In total, we identified 143 RCTs with 329 unique study arms published between January 2008 and August 2019, yielding a total of 12,532 participants with data available for analysis [1-3, 5-21, 23, 25, 27-44, 48-64, 66, 68, 70, 71, 74-102, 104, 108-110, 112-132, 134-138, 140, 141, 143-151, 153-162, 164, 165]. The four most common brachial plexus blocks were interscalene (5417 participants), axillary (3301), infraclavicular (2445), and supraclavicular (1840 participants).…”
Section: Methodsmentioning
confidence: 99%
“…Also, high perineural sodium concentration may displace the local anesthesia from the bindings. [ 19 23 ] Citric acid would be helpful to maintain lower pH Hypercalcium condition: Higher amount of Ca ions around nerve cells makes the membrane hyperpolarized and low affinity for initiation of rest phase. [ 18 24 ] Therefore, calcium gloconate 10% was registered in this pharmaceutical solution.…”
Section: Methodsmentioning
confidence: 99%
“…Also, high perineural sodium concentration may displace the local anesthesia from the bindings. [ 19 23 ] Citric acid would be helpful to maintain lower pH…”
Section: Methodsmentioning
confidence: 99%